2022
DOI: 10.1093/jxb/erac392
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of anthocyanin and proanthocyanidin and their regulation in determining chickpea flower and seed coat colour

Abstract: Flower and seed coat colour are important agronomic traits in chickpea (Cicer arietinum L.). Cultivated chickpeas are of two types namely, desi (dark seeded, purple flower) and kabuli (light colour seeded, white flower). There has been limited information about the molecular mechanism underlying the colour variation of flower and seed coats in desi and kabuli chickpea. We profiled the anthocyanin and proanthocyanidin (PA) contents in chickpea flowers and seed coats. Tissue-specific silencing of two genes encod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Variation in the gene coding region is a common allelic variation. Similarly, the DTX / MATE allele was also found in chickpeas, with variations in the corresponding transporting activity of Cy3G (Pal et al, 2023). These results indicate that the differences in anthocyanin and PA among different varieties are closely related to the natural variation of DTX/MATE.…”
Section: Discussionmentioning
confidence: 87%
“…Variation in the gene coding region is a common allelic variation. Similarly, the DTX / MATE allele was also found in chickpeas, with variations in the corresponding transporting activity of Cy3G (Pal et al, 2023). These results indicate that the differences in anthocyanin and PA among different varieties are closely related to the natural variation of DTX/MATE.…”
Section: Discussionmentioning
confidence: 87%
“…The findings of previous studies have indicated that anthocyanin transport proteins may play roles in plant vacuoles (Han et al 2022, Pal et al 2023), and PpGST1 , MdGSTF6 , and LcGST4 have been identified as genes encoding proteins associated with the transport of anthocyanins (Hu et al 2016, Jiang et al 2019, Zhao et al 2020). Moreover, LhDTX35 (encoding a MATE) has been established to play a key role in regulating the accumulation of anthocyanins (Xu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the key regulators, the Transparent Testa ( TT ) gene plays a crucial role in proanthocyanidin biosynthesis, influencing various seed color types in plants. Extensive investigations of the TT gene have been conducted in various plants species, notably in the model, Arabidopsis (Marinova et al., 2007; Zhao & Dixon, 2009) and in legume species such as Medicago (Li et al., 2016; Liu et al., 2014; Zhao & Dixon, 2009), soybean (Lu et al., 2021), Brassica (Li et al., 2012; Yu, 2013), and chickpea (Pal et al., 2022). Mutants lacking functional TT genes, such as tt4 , tt12 , and tt19 , have transparent seed coats due to the absence of proanthocyanidin accumulation (Debeaujon et al., 2001, 2003; Marinova et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Much of our understanding on the molecular mechanisms governing flavonoid biosynthesis came from the genetic studies on Arabidopsis mutants (Appelhagen et al., 2011, 2015; Baudry et al., 2004; Debeaujon et al., 2001, 2003; Gonzalez et al., 2016; Marinova et al., 2007). However, limited efforts have been made to understand the genetic basis of seed color variation in chickpea, with most studies focusing on association analysis and genetic mapping of QTLs governing the trait using a smaller set of diversity panel and mapping population (Bajaj, Das, et al., 2015; Hossain et al., 2010; Kazan et al., 1993; Pal et al., 2022; Penmetsa et al., 2016). None of the low‐resolution QTLs identified for seed color trait has been validated in diverse genetic backgrounds across multiple environments or fine‐mapped through map‐based cloning to delineate the functional allele(s) of gene(s) regulating the seed color variation in chickpea.…”
Section: Introductionmentioning
confidence: 99%